2019
DOI: 10.1038/s41467-019-13105-5
|View full text |Cite|
|
Sign up to set email alerts
|

CDK2-mediated site-specific phosphorylation of EZH2 drives and maintains triple-negative breast cancer

Abstract: Triple-negative breast cancer (TNBC), which lacks estrogen receptor α (ERα), progesterone receptor, and human epidermal growth factor receptor 2 (HER2) expression, is closely related to basal-like breast cancer. Previously, we and others report that cyclin E/cyclin-dependent kinase 2 (CDK2) phosphorylates enhancer of zeste homolog 2 (EZH2) at T416 (pT416-EZH2). Here, we show that transgenic expression of phospho-mimicking EZH2 mutant EZH2T416D in mammary glands leads to tumors with TNBC phenotype. Coexpression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(51 citation statements)
references
References 56 publications
2
49
0
Order By: Relevance
“…Moreover, levels of components (EZH2 and SUZ12) of PRC2 and H3K27me3 were reduced following T 3 treatment of HepG2-TR cells. On the other hand, previous studies have documented that cyclin E/CDK2 phosphorylates EZH2 at T416 (pT416-EZH2) [48]. Phosphorylation of EZH2 at T416 promotes its ability to induce triple-negative breast cancer cell migration, invasion and tumor formation in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, levels of components (EZH2 and SUZ12) of PRC2 and H3K27me3 were reduced following T 3 treatment of HepG2-TR cells. On the other hand, previous studies have documented that cyclin E/CDK2 phosphorylates EZH2 at T416 (pT416-EZH2) [48]. Phosphorylation of EZH2 at T416 promotes its ability to induce triple-negative breast cancer cell migration, invasion and tumor formation in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…69 This CDK is a potential target for TNBC treatment, as it has been observed to promote tumourogenesis in vivo , with inhibition inducing ER expression in TNBC MDA-MB-231 cells, sensitising them to ER-targeted therapies. 70 Overactivity of tCDKs can lead to transcriptional addiction, where cancers become “addicted” to transcription of genes that drove the initial stages of tumour formation, but remain necessary for cancer cell survival after tumourogenesis. 71 Their knockout may thus induce tumour death.…”
Section: Therapeutic Potential Of Crispr In Bcmentioning
confidence: 99%
“…[ 44–47 ] ER α is the target of tamoxifen, and BCs that lose ER α expression are undoubtedly less responsive to tamoxifen therapy. [ 37,48 ] In addition, activation of the PI3K‐AKT pathway induces tamoxifen resistance mainly through the following aspects: 1) the PI3K‐AKT pathway can lead to a decrease in ER α expression, [ 27,49 ] and 2) the PI3K‐AKT pathway promotes the expression of a series of genes involved in cell proliferation, which allows cells to escape the inhibitory effects of tamoxifen. [ 3 ] Our study first confirmed the dual function of miR‐22 in breast cancer tamoxifen resistance: the accumulation of miR‐22 in BCs not only results in ER α downregulation but also in PI3K‐AKT pathway activation via the downregulation of PTEN, a major negative regulator of the PI3K‐Akt pathway.…”
Section: Discussionmentioning
confidence: 99%